2020
DOI: 10.1002/hep4.1468
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Childhood Cholestasis in Alagille Syndrome: Results of a Multicenter Observational Study

Abstract: Alagille syndrome (ALGS) is an autosomal dominant multisystem disorder with cholestasis as a defining clinical feature. We sought to characterize hepatic outcomes in a molecularly defined cohort of children with ALGS‐related cholestasis. Two hundred and ninety‐three participants with ALGS with native liver were enrolled. Participants entered the study at different ages and data were collected retrospectively prior to enrollment, and prospectively during the study course. Genetic analysis in 206 revealed JAGGED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 30 publications
2
75
3
Order By: Relevance
“…The G lobal AL agille A lliance (GALA) study, which was described in a congress abstract reporting on a large cohort of patients with ALGS, found that 10‐year native liver survival was no more than 70% 28 . This is further illustrated in published data from 293 patients with ALGS and cholestasis in the multicentre, prospective Chi ldhood L iver D isease Re search N etwork (ChiLDReN) study, in which estimated liver transplant‐free survival was 24% at age 18.5 33 . The experience is similar for patients with PFIC.…”
Section: Burden Of Cholestatic Liver Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…The G lobal AL agille A lliance (GALA) study, which was described in a congress abstract reporting on a large cohort of patients with ALGS, found that 10‐year native liver survival was no more than 70% 28 . This is further illustrated in published data from 293 patients with ALGS and cholestasis in the multicentre, prospective Chi ldhood L iver D isease Re search N etwork (ChiLDReN) study, in which estimated liver transplant‐free survival was 24% at age 18.5 33 . The experience is similar for patients with PFIC.…”
Section: Burden Of Cholestatic Liver Diseasesmentioning
confidence: 90%
“…28 This is further illustrated in published data from 293 patients with ALGS and cholestasis in the multicentre, prospective Childhood Liver Disease Research Network (ChiLDReN) study, in which estimated liver transplant-free survival was 24% at age 18.5. 33 The experience is similar for patients with PFIC. The 10-year native liver survival among patients with ATP8B1-and ABCB11-deficient PFIC, as reported by the NAtural course and Prognosis of PFIC and Effect of biliary Diversion (NAPPED) consortium, was 46%-51%.…”
Section: Burden Of Chole S Tatic Liver Dise a Se Smentioning
confidence: 92%
“…Liver disease in ALGS, like the other associated clinical manifestations, is highly variable, ranging from mild biochemical abnormalities to profound cholestasis associated with malnutrition, fat-soluble vitamin deficiencies, refractory pruritus, and xanthomas. In some large series, the rate of progression to liver transplantation was found to be 20% to 30% (27), although more recent reports suggest the numbers are higher, especially in patients presenting with cholestatic liver disease early in life (37). Patients with ALGS are also at risk for development of hepatocellular carcinoma (38).…”
Section: Liver Disease In Algsmentioning
confidence: 99%
“…Alagille syndrome is an autosomal dominant disorder arising from mutations in the JAGGED1 or NOTCH2 genes which causes multi-system malformations including impaired formation of bile ducts in embryonic development (Mitchell et al, 2018). According to a recent prospective study, only about 24% of children with bile duct paucity reach adulthood without a liver transplant, indicating the serious need for alternative therapies (Kamath et al, 2020). Interestingly, the penetrance of these mutations varies widely leading to variability in the extent of cholestasis and disease presentation, with some patients even showing spontaneous recovery.…”
Section: Introductionmentioning
confidence: 99%